Clinical, Laboratory, and Management Profile in Patients of Liver Abscess from Northern India. (4th June 2014) - Ghosh, Soumik; Sharma, Sourabh; Gadpayle, A. K.; Gupta, H. K.; Mahajan, R. K.; Sahoo, R.; Kumar, Naveen
Abstract : Objective . To describe the clinical profile, microbiological aetiologies, and management outcomes in patients with liver abscess. Methods . A cross-sectional study was conducted from May, 2011, to April, 2013, on 200 consecutive liver abscess patients at PGIMER and Dr. RML Hospital, New Delhi. History, examination, and laboratory investigations were recorded. Ultrasound guided aspiration was done and samples were investigated. Chi-square test and multivariate regression analysis were performed to test association. Results . The mean age of patients was 41.13 years. Majority of them were from lower socioeconomic class (67.5%) and alcoholic (72%). The abscesses were predominantly in right lobe (71%) and solitary (65%). Etiology of abscess was 69% amoebic, 18% pyogenic, 7.5% tubercular, 4% mixed, and 1.5% fungal. Percutaneous needle aspiration was done in 79%, pigtail drainage in 17%, and surgical intervention for rupture in 4% patients. Mortality was 2.5%, all reported in surgical group. Solitary abscesses were amoebic and tubercular whereas multiple abscesses were pyogenic (P = 0.001 ). Right lobe was predominantly involved in amoebic and pyogenic abscesses while in tubercular abscesses left lobe involvement was predominant (P = 0.001 ). Conclusions . The commonest presentation was young male, alcoholic of low socioeconomic class having right lobe solitary amoebic liver abscess. Appropriate use of minimally invasive drainage techniques reduces mortality.